Kinematic aspects of block phase technique in sprinting - Bezodis, N.; Salo, A.; Trewartha, G. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study investigated kinematic aspects of block phase technique during the sprint start and their relationships with performance amongst a heterogeneous group of 16 sprinters. Lower limb kinematics in the 'set' position were not associated with block phase performance (average horizontal external power). During block exit a greater rear leg push, in particular from the hip, appeared important for performance. The front leg extended in a proximal-to-distal fashion, with more rapid hip extension again facilitating performance. Striving to achieve higher levels of block phase performance did not appear to negatively affect the first flight phase or the configuration of the sprinters at first touchdown. Sprinters should therefore be encouraged to maximise hip extensions in the blocks and use their rear leg drive to achieve a powerful block exit.